Hjalmar Lundbohm : En studie om ledarskap inom LKAB 1898-1921 - Persson, Curt (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2015)
The thesis has as main purpose to study the influences that affected LKAB's first manager Hjalmar Lundbohm (1855-1926) in his leadership, both in mining operations and within the social structure, and how Lundbohm as a leader utilized his network. The study is implemented as a scientific biography. Previous research has dealt with Lundbohm’s role as leader and community builder in peripheral ways within larger histories, but no comprehensive analysis of Lundbohm as a leader and network builder has been made.With the focus on an in-depth description of Lundbohm as a person and his role as a leader, the thesis further aims to contribute to a better understanding of the prerequisites that existed when the mining activities in Kiruna and Tuolluvaara started and as the two societies were built up. The hope is also that the analysis of this leadership can serve as a description of the individual leader’s significance for corporate development and leader’s engagement in social issues.Lundbohm appeared as leader at a time when the patriarchal leadership was about to be replaced by a leadership under greater professionalisation, where the requirement of specialist expertise in the specific business area had increased. At the same time Lundbohm’s authority as a leader in LKAB was questioned even before the First World War, because of the outdated patriarchal leadership style he exercised.Outside of LKAB Lundbohm was perceived as a strong patriarchal leader. In connection with his burial some of the speakers expressed that during Lundbohm’s life he had intentionally cultivated an image of himself as the patriarchal protector as well as leader of the mining community. His legendary status was already solidified immediately after his death.The thesis questions the image of Kiruna as a utopian society, revealing other perspectives which expose the differences in standard between the different social components, town plan, SJ residential areas, LKAB's own residence establishment, and Tuolluvaara.Keywords: patriarchal, network, ...